POLA MAKAN, AKTIVITAS FISIK, DAN STATUS GIZI SISWA SMA NEGERI 1 SINGARAJA DI MASA PANDEMI COVID-19 - Kumara, Kadek Dhiyo Mamhista; Putra, I Wayan Gede Artawan Eka (ARCHIVE OF COMMUNITY HEALTH; Vol 9 No 1 (2022): April 2022, 2022)
The policy of learning from home as the effect of pandemic situation can change the diet, physical activity, and the nutritional status of students. This study is an observational study with a cross-sectional design used in SMA Negeri 1 Singaraja with a sample size of 283 students. This study was collecting diet, physical activity, and nutritional status data using an online questionnaire. Data were analyzed descriptively. The results showed that most of the students had a good diet (61,48%), did light physical activity (84,81%), and had normal nutritional status (77,74%). Most students often consume vegetables (>50%), but fruit consumption was still lacking (<10,00%). The consumption of sugary drinks and junk food in adolescents was quite high (>50%). We suggest students to apply a balanced nutritious diet and continue to do physical activity during the pandemic so that they can achieve optimal nutritional and health status. Keywords: Adolecent, Diet, Physical Activity, Nutritional Status